Facile fabrication of Au/SiO2 nanostructures from 1D to 3D nanotubes networks using templating methods - Drault, Fabien; Eloy, Pierre; Demoustier-Champagne, Sophie; Hermans, Sophie (Catalysis today, 2024)
We report a facile fabrication method for free-standing gold (Au) or silica (SiO2) nanotubes with highly controlled geometry and ordered porosity (pNTs) and their nanostructuration from 1D to 3D interconnected networks. A dual nano-templating method was employed using polycarbonate membranes as first mold for the nanotubes, together with stacked polystyrene (PS) nanospheres to induce porosity. The pore size in the final nanotube walls can be controlled by adjusting the ratio x (where x = internal diameter of the nanotube divided by the diameter of the nanospheres), which determines the packing order of the spheres in the tubes. Then, gold electroless or silica sol-gel deposition were performed in the dual-templated structure to obtain Au or SiO2 pNTs, respectively. The templates removal was performed in one step using dichloromethane. A further functionalization of the silica pNTs with Au NPs using the electroless deposition method was successfully implemented as well, leading to a homogeneous dispersion of Au NPs with a size of 11 ± 2.8 nm. Chemical compositions and optical properties of the so-obtained materials were determined by XPS and UV–visible analyses, respectively. [Display omitted]